High cortisol levels as a risk factor for athletes poor sleep quality in training centers - Agustini, Ni Nyoman Mestri; Nuartha, A. A. B. N.; Laksmidewi, A. A. A Putri (International Journal of Research in Medical Sciences, 2025)
Background: Intense training in athletes may able to disrupt the HPA axis which leads to increased cortisol levels and low- level quality to sleep. This study investigates whether elevated cortisol levels are a risk factor for low-level sleep quality in athletes. Methods: This case-control study was conducted from June to November 2017 at a training centre in Denpasar. Subjects included athletes are from athletics, badminton, and bicycle racing who are preparing for a national tournament. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), and serum cortisol levels were assessed. Bivariate and multivariate analyses were performed to determine the relationship between cortisol levels and sleep quality. Results: The study included 64 athletes. Cortisol levels were significantly higher in athletes with low-level sleep quality (270.86±93.43 nmol/l) compared to those with good sleep quality (195.84±61 nmol/l). High cortisol levels were strongly associated with low-level sleep quality (OR 7.67; 95% CI 2.52-23.28; p<0.001). Multivariate analysis confirmed high cortisol levels as an independent risk factor for low-level sleep quality (OR 8.19; 95% CI 2.59–25.89; p<0.001). Elevated cortisol levels are a significant independent risk factor for low-level sleep quality in athletes undergoing intense training. Conclusions: Elevated cortisol independently predicted poor sleep-in athletes undergoing intense physical training.